Computational modeling for fluid flow and interfacial transport - Shyy, W. (Wei) (Transport processes in engineering ;, 1994)
Transport processes are often characterized by the simultaneous presence of multiple dependent variables, multiple length scales, body forces, free boundaries and strong non-linearities. The various computational elements important for the prediction of complex fluid flows and interfacial transport are presented in this volume. Practical applications, presented in the form of illustrations and examples are emphasized, as well as physical interpretation of the computed results. The book is intended as a reference for researchers and graduate students in mechanical, aerospace, chemical and mater.